DEVELOPMENT OF PLANT ACCOUNTING RESEARCH: EVIDENCE FROM INDONESIA 2017-2021 WITH SUSTAINABILITY VALUE CREATION - ,; ,; ,; ,; ,; ,; ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 9 No 1 (2025): Bilancia : Jurnal Ilmiah AkuntansiDO - 10.35145/bilancia.v9i1.4901, 2025)
The importance of the quality of financial information so that readers of financial statements can know exactly the fair value of a plant asset. The purpose of this study is to see the development of crop accounting research and to add methods to assess the fair price of plants. The research method uses content analysis from articles for 2017-2021 based on the Harzing's Publish or Perish application. There are three articles that can be used for this research. The results of the study indicate that the determination of the fair price of plants in the financial statements is very important in order to avoid asymmetric information. The results also show that assessing the fair price of plant assets can be done by looking at the future selling price of the asset. Meanwhile, the excess of the fair value assessment will be subject to a final income tax of ten percent. To create sustainable value in crop accounting, it is necessary to create regulations or develop PSAK 69. Recommendations to accountants to present plant assets at fair value to make it easier for shareholders to make decisions and update accounting insights, especially in PSAK which can change at any time in order to make adjustments to the accounts in the financial statements and make newer research for the development of insights scientific research for researchers. Pentingnya kualitas informasi keuangan agar pembaca laporan keuangan dapat mengetahui dengan tepat nilai wajar dari suatu aset tanaman. Tujuan penelitian ini untuk melihat perkembangan penelitian akuntansi tanaman dan menambahkan metode untuk menilai harga wajar dari tanaman. Metode penelitian menggunakan analisis konten dari artikel tahun 2017-2021 berdasarkan aplikasi Harzing’s Publish or Perish . Terdapat tiga buah artikel yang dapat digunakan untuk penelitian ini. Hasil penelitian menunjukkan bahwa penetapan harga wajar tanaman di laporan keuangan sangat penting agar tidak adanya informasi asimetris. Hasil penelitian juga menunjukkan bahwa menilai harga wajar dari aset tanaman dapat dilakukan dengan melihat harga jual masa depan dari aset tersebut. Sedangkan selisih lebih atas penilaian nilai wajar tersebut akan dikenakan pajak penghasilan final sebesar sepuluh persen. Untuk penciptaan nilai keberlanjutan pada akuntansi tanaman, diperlukan membuat regulasi atau mengembangkan PSAK 69. Rekomendasi kepada akuntan untuk menyajikan aset tanaman dengan nilai wajar untuk mempermudah pemegang saham dalam mengambil keputusannya dan memperbarui wawasan akuntansi terutama di PSAK yang bisa berubah sewaktu-waktu agar membuat penyesuaian kembali terhadap akun-akun di laporan keuangan dan membuat penelitian yang lebih baru untuk pengembangan wawasan ilmiah bagi peneliti.